2014
DOI: 10.1371/journal.pone.0095355
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signaling 2 (RGS2) and RGS4 Form Distinct G Protein-Dependent Complexes with Protease Activated-Receptor 1 (PAR1) in Live Cells

Abstract: Protease-activated receptor 1 (PAR1) is a G-protein coupled receptor (GPCR) that is activated by natural proteases to regulate many physiological actions. We previously reported that PAR1 couples to Gi, Gq and G12 to activate linked signaling pathways. Regulators of G protein signaling (RGS) proteins serve as GTPase activating proteins to inhibit GPCR/G protein signaling. Some RGS proteins interact directly with certain GPCRs to modulate their signals, though cellular mechanisms dictating selective RGS/GPCR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…RGS8 directly binds to the N terminus and the third intracellular loop of the M1-muscarinic acetylcholine receptor to regulate receptor-mediated Ga q signaling [33]. RGS2 and RGS4 additionally inhibit PAR1-mediated Ga signaling through interactions with distinct Ga proteins [14]. ERK activity was determined by immunoblotting using p-ERK and total ERK antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RGS8 directly binds to the N terminus and the third intracellular loop of the M1-muscarinic acetylcholine receptor to regulate receptor-mediated Ga q signaling [33]. RGS2 and RGS4 additionally inhibit PAR1-mediated Ga signaling through interactions with distinct Ga proteins [14]. ERK activity was determined by immunoblotting using p-ERK and total ERK antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Gpr161, an orphan GPCR, contains a motif for A-kinase anchoring protein in its C-terminal tail and binds the regulatory subunits of PKA, leading to the modulation of cAMP signaling [13]. Using a bioluminescence resonance energy transfer (BRET) technique, we previously reported that RGS2 and RGS4 interact with PAR1 in a Ga-dependent manner to regulate PAR1/Ga-mediated signaling [14]. Using a bioluminescence resonance energy transfer (BRET) technique, we previously reported that RGS2 and RGS4 interact with PAR1 in a Ga-dependent manner to regulate PAR1/Ga-mediated signaling [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The yellow fluorescent fusion protein expression vector Venus-C1 and the Renilla luciferase (Rluc) fusion protein expression vectors were used [52]. Construction of luciferase fusion protein vector mCx45-Rluc was achieved by insertion of the PCR product of the mouse Cx45 into vector Rluc-N1 at XhoI and HindIII enzyme sites upstream of luciferase.…”
Section: Methodsmentioning
confidence: 99%
“…Other observations have shown that RGS4 and RGS2 are recruited to the plasma membrane by G proteins and/or the expressed receptors [8,10]. Recent evidence indicates that RGS2 and RGS4 interact directly with PAR1 in a Ga-dependent manner to modulate PAR1/Ga-mediated signalling [23]. All these observations indicate that selectivity of RGS proteins for a given GPCR or G protein is influenced by different parameters ranging from the nature and abundance of G and RGS proteins present in a certain cellular milieu to the activation state of each receptor.…”
Section: Introductionmentioning
confidence: 99%